2017
DOI: 10.2136/vzj2016.10.0095
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Inhibitors and Their Remediation Potential on Brine‐Contaminated Soils

Abstract: Core Ideas Brine‐contaminated soils require remediation in many oil‐producing regions. A crystallization inhibitor induced harvestable salt efflorescence on contaminated soils. Crystallization inhibitors can be part of the remediation effort on brine‐contaminated soils. We hypothesize that a crystallization inhibitor will induce harvestable salt efflorescence on the surface of brine‐contaminated soils. If proven, the harvest of effloresced salts will provide a novel method for remediating brine spills. Our o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
(73 reference statements)
0
15
1
Order By: Relevance
“…In laboratory experiments utilizing a surficial application of the crystallization inhibitor to NaCl‐contaminated sandy loam, loam, and silty clay soils, this method was found to reduce the mass of NaCl (34.75 g total) in the soil by 460, 570, and 290 g kg −1 (grams harvested salt at the soil surface per total grams of NaCl applied to the soil), respectively (Klaustermeier et al., 2017). In subsequent experiments, the authors found that the re‐application of the crystallization inhibitor following the initial harvest of salts produced little to no additional salt growth, indicating that this method may only be applicable for the partial remediation of brine‐impacted soils (Klaustermeier et al., 2017; Swallow & O'Sullivan, 2019). Furthermore, it was found that the effectiveness of the crystallization inhibitor was limited at low salt concentrations (<0.5 M NaCl) and produced little efflorescence when either soils were only dominated with SO 4 ‐based salts or when soil Ca levels where high enough to form Ca‐based crusts before NaCl hopper crystal growth could initiate (Klaustermeier et al., 2017).…”
Section: Novel Experimental Remediation Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In laboratory experiments utilizing a surficial application of the crystallization inhibitor to NaCl‐contaminated sandy loam, loam, and silty clay soils, this method was found to reduce the mass of NaCl (34.75 g total) in the soil by 460, 570, and 290 g kg −1 (grams harvested salt at the soil surface per total grams of NaCl applied to the soil), respectively (Klaustermeier et al., 2017). In subsequent experiments, the authors found that the re‐application of the crystallization inhibitor following the initial harvest of salts produced little to no additional salt growth, indicating that this method may only be applicable for the partial remediation of brine‐impacted soils (Klaustermeier et al., 2017; Swallow & O'Sullivan, 2019). Furthermore, it was found that the effectiveness of the crystallization inhibitor was limited at low salt concentrations (<0.5 M NaCl) and produced little efflorescence when either soils were only dominated with SO 4 ‐based salts or when soil Ca levels where high enough to form Ca‐based crusts before NaCl hopper crystal growth could initiate (Klaustermeier et al., 2017).…”
Section: Novel Experimental Remediation Strategiesmentioning
confidence: 99%
“…In subsequent experiments, the authors found that the re‐application of the crystallization inhibitor following the initial harvest of salts produced little to no additional salt growth, indicating that this method may only be applicable for the partial remediation of brine‐impacted soils (Klaustermeier et al., 2017; Swallow & O'Sullivan, 2019). Furthermore, it was found that the effectiveness of the crystallization inhibitor was limited at low salt concentrations (<0.5 M NaCl) and produced little efflorescence when either soils were only dominated with SO 4 ‐based salts or when soil Ca levels where high enough to form Ca‐based crusts before NaCl hopper crystal growth could initiate (Klaustermeier et al., 2017). Irrespective of challenges, the potential use of these chemicals, especially on spills on well pads where soil removal may not be possible, deserves further exploration.…”
Section: Novel Experimental Remediation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In semiarid climates such as the Williston Basin, where annual evaporative demand is often four times that of annual precipitation, the potential for resalinization of the topsoil through upward capillary rise causes this method to be time‐intensive and costly while often achieving limited results (Harris et al, 2005). Given the limitations of traditional methods, novel forms of in situ remediation from the soil surface through the use of crystallization inhibitors and the capillary rise of water and dissolved salts have been presented in the literature with promising results (Klaustermeier et al, 2017; Swallow and O'Sullivan, 2019). The objective of this proof‐of‐concept study was to determine the efficacy of using highly absorbent “wicking” materials to draw water and dissolved salts from the soil profile as a means of permanent salt removal (Fig.…”
Section: Figmentioning
confidence: 99%
“…Previous research also reported applying certain chemical amendments. For example, several studies showed that soil amendment with ferrocyanide could be a potential option for removing salt from soil surface by efflorescing salt as soft, hollow hopper crystals (Daigh & Klaustermeier, 2016; Klaustermeier, Daigh, Limb, & Sedivec, 2017). However, applying this method would generate hypertoxic hydrocyanic acid.…”
Section: Introductionmentioning
confidence: 99%